The Role of Artificial Intelligence in Social Media Marketing Activities on Online Purchase Intention of the Digital Generation in Indonesia - Aditya Yudanegara; Fansuri Munawar; Ayuningtyas Yuli Hapsari (Transpublika Publisher, 2026)
With social media engagement and brand trust as mediating factors, this study analyzes the role of artificial intelligence (AI) in social media marketing and its influence on the online purchase intention of Indonesia’s digital generation. According to the Stimulus-Organism-Response (SOR) framework, AI is conceptualized as a technological stimulus, engagement and brand trust as internal psychological states, and purchase intention as the resulting behavioral response. A quantitative approach was adopted using a structured online questionnaire distributed via Instagram, TikTok, and WhatsApp. A purposive sampling method was applied to target people aged 18 to 40 with regular social media use and prior exposure to AI based features. After analyzing 485 valid responses through Partial Least Squares Structural Equation Modeling (PLS SEM), the findings indicate that AI has a strong positive effect on both social media marketing activities and consumer engagement. Enhanced social media marketing activities lead to greater engagement, which then positively shapes brand trust and purchase intention. Importantly, engagement and brand trust mediate the link between AI and purchase intention. These results verify that AI driven consumer decision making unfolds through a sequential pathway that includes cognitive, emotional, and relational factors. Theoretically, this study contributes by integrating AI, social media marketing, engagement, and brand trust into a unified framework within an emerging digital economy context. Practically, the findings offer actionable insights for marketers seeking to design AI-driven strategies that strengthen engagement, foster trust, and increase online purchase intention among digitally active consumers.